2015
DOI: 10.1556/oh.2015.30087
|View full text |Cite
|
Sign up to set email alerts
|

The role of chromogranin-A and its derived peptide, WE-14 in the development of type 1 diabetes mellitus

Abstract: A kromogranin-A a granincsaládba tartozó fehérje, amelyet neuroendokrin sejtek termelnek és ezek szekréciós granulumaiból származik. A kromogranin-A-ból számos, mind ez idáig kevésbé tisztázott funkciójú fehérje képződik. Jelenleg a kromogranin-A vérben mérhető szintjének meghatározását elsősorban neuroendokrin daganatok laboratóriumi diagnosztikájában használják. A legfrissebb kutatások alapján azonban úgy tűnik, a kromogranin-A-ból szár-mazó WE-14 nevű fehérjének szerepe lehet az 1-es típusú cukorbetegség ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
(46 reference statements)
1
2
0
1
Order By: Relevance
“…We did not observe one specific trend for all the indicated substances. This finding confirms previous reports showing that these substances could be associated with the T1D course and various late complications [ 26 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We did not observe one specific trend for all the indicated substances. This finding confirms previous reports showing that these substances could be associated with the T1D course and various late complications [ 26 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a number of studies, selected biologically active substances were indicated as contributing to the etiology (IAPP [ 16 , 31 , 32 , 33 , 34 , 35 , 36 ], proIAPP [ 17 , 18 , 37 ], I-FABP [ 24 ]), course (CST [ 38 , 39 ], ChgA [ 40 , 41 , 42 ]) or the development of various complications (neuropathy—NGF [ 43 , 44 , 45 ], cardiovascular complications—PAF [ 26 , 46 , 47 ], and cardiovascular complications and nephropatia—UMOD [ 28 , 48 , 49 ]). In the current study, we assessed the diagnostic usefulness of these indicators present in T1D patients’ sera and confirmed statistically significant differences between their concentrations in the group of children with T1D and healthy children, but only some of them (NGF, ChgA, CST and PAF) were affected by disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have revealed that CgA may affect blood pressure, obesity, fat levels and pancreatic beta cells. [37][38][39][40] The study of Kogawa et al, on type 2 patients with diabetes, showed that the level of CgA in the saliva and serum of these patients was significantly higher than in the control group. 29 The exact mechanisms of aging and sex and their effects on genetic polymorphisms and serum levels of CgA are not completely understood in subjects with MetS.…”
Section: Discussionmentioning
confidence: 94%
“…a pankreasztatin, a β-granin, a kromosztatin, a vazosztatin és a parasztatin (1. ábra). 7 Egyes feltevések szerint további, mind ez ideig még fel nem fedezett hasadási termékek is képződhetnek belőle. 3,8…”
Section: A Kromogranin-a Biológiai Jellemzőiunclassified